Pituitary Apoplexy: A Retrospective Study of 33 Cases From a Single Center - Falhammar, Henrik; Tornvall, Sofia; Höybye, Charlotte (Frontiers in Endocrinology, 2021)
Purpose Acute symptomatic pituitary apoplexy is a rare and potentially life-threatening condition. However, pituitary apoplexy can also present with milder symptoms and stable hemodynamics. Due to the rarity of this inhomogeneous condition, clinical studies are important to increase the knowledge. Methods We retrospectively reviewed all consecutive cases of pituitary apoplexy being admitted between January 1st, 2005 and December 31st, 2019 at the Karolinska University Hospital, Stockholm, Sweden, for symptoms, results of magnetic resonance (MRI), biochemistry, management and mortality. Results Thirty-three patients were identified with pituitary apoplexy, 18 were men (55%) and mean age was 46.5 (17.2) years. The incidence of symptomatic pituitary apoplexy was 1.6 patients/year (0.76 patients/1,000,000 inhabitants/year). The majority presented with headache (n=27, 82%) and hormonal deficiencies (n=18, 55%), which were most frequent in men. ACTH deficiency was present in nine patients (27% but 50% of those with hormonal deficiencies). All had the characteristic findings on MRI. Only three patients (9%) required acute pituitary surgery, while eight were operated after more than one week. Seven (21%) were on antithrombotic therapy. None of the patients died in the acute course. During follow-up (7.6 ± 4.3 years) none of the hormonal deficiencies regressed and 3 patients died from non-related causes. Conclusion Our study confirmed the rarity and the symptoms of this condition. Surprisingly, only 3 patients needed acute neurosurgical intervention, perhaps due to milder cases and a general intensified treatment of precipitating factors. An early awareness and in severe cases decision on pituitary surgery is of utmost importance to avoid severe complications.